EVALUASI IMPLEMENTASI KURIKULUM PROTOTIPE (KEPMENDIKBUDRISTEK NO. 162/M/2021) DI UPTD SMP NEGERI 1 DATUK LIMA PULUH KABUPATEN BATUBARA DENGAN MODEL CIPP - Tobok Luhut Situmorang; Rosmala Dewi; Yuniarto Mudjisusatyo; Eka Daryanto (Jurnal Education and Development, 2022)
This study aims to significantly implement the prototype curriculum at Junior High School (SMP) level. The evaluation results from this study is expected to provide the appropriate input in the implementation of the prototype curriculum. This research was conducted at UPTD SMP Negeri 1 Datuk Lima Puluh Batubara Regency involving 21 teachers and 205 student and the evaluation model used is CIPP (Context, Input, Process, Output) by Stufflebeam. The instrument used in the study was a questionnaire compiled based on CIPP aspects and indicators on the prototype and the data were analyzed using simple descriptive statistics. The results of this study found that facilities and infrastructure were considered good by as many as 74.01% of teachers and students while the understanding of teachers and students as well as parental involvement is in the category of less than 47%. In addition, from the input aspect, the procurement of books received a very good response, which was 96.40%. However, less than 43% of respondents considered that the guidance provided to teachers was in the poor category and the process aspect received a poor response from respondents, which was less than 49%. A total of 69.37% of respondents gave a good response in the product aspect category. Implementation of the prototype curriculum needs to pay attention to the readiness and quality of teachers, schools, and other aspects. In addition, the class level in the prototype curriculum can be replaced with the term "phase" because learning outcomes are at the phase level and not at the class level. The expert trainers should be presented directly to schools and improvements in process aspects can be made by defining a clear role in the policy.